Abai’s Philosophy and Literature in the Context of World Philosophical Thought - S.D., Abisheva; M.M., Khavaidarova; Massimo , Maurizio (Journal of Ecohumanism, 2025)
The article is devoted to the philosophical and literary aspects of the work of Abai Kunanbayev, one of the greatest thinkers and poets of Kazakhstan, in the context of the world philosophical tradition. The work examines how Abai’s ideas relate to the teachings of leading philosophers of the East and West, such as Confucius, Socrates, Leo Tolstoy and Jean-Jacques Rousseau. Particular attention is paid to the philosophical categories presented in Abai’s works, such as reason, conscience, faith, knowledge, man, labor and society, and their interrelations. The methodological basis of the study is hermeneutic, comparative and historical-philosophical analyses. The study revealed that Abai’s philosophy is a synthesis of national traditions and universal humanistic values, and is also relevant in modern society. The work emphasizes the importance of Abai’s philosophy as an important element of world thought and the cultural identity of Kazakhstan.